Artificial intelligence enabled additive manufacturing system using 5G and industrial IoT. (5th September 2022) - Shirwaikar, Rudresh Deepak; Tandon, Aditya; Kumar, K. Sathesh; Nag, M.V. Aditya; Jos, Bobin Cherian; Jos, Bos Mathew
There are numerous types of additive manufacturing equipment, ranging from basic RepRap machinery to sophisticated fused metal depositing systems. Lightweight items, lower errors, minimum tool costs, optimum components usage, and feasible manufacturing method are depending on field implementation. Smart agents powered by AI can help minimise the number of people needed to raise AM productivity with the simultaneous improvement in source usage. The present state of AI-enabled AM item enhancement is explored in this paper. Artificial intelligence (AI), digitalised reality, internet of things (IoT), blockchain, driverless cars, and future innovations are all dependent on 5G's lightning-fast connectivity and minimal latency. The launch of 5G is much more beyond a generational shift; it ushers in a new period of opportunities for the IT sector. Based on the original objectives and expectations of both domains, the goal of this article is to develop a method that integrates AI with additive manufacturing systems.